ANALISIS EFEKTIVITAS DAN KOTRIBUSI PAJAK BUMI DAN BANGUNAN DAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN TERHADAP PENDAPATAN ASLI DAERAH KOTA YOGYAKARTA TAHUN 2012-2016 - Noprianto Iwan Putra (JURNAL EKOBIS DEWANTARA, 2018)
The purpose of this research is to know the level of effectiveness and contribution of Land and Building Tax (PBB) and Customs Acquisition of Land and Building Rights (BPHTB) to Local Original Income (PAD) of Yogyakarta Year 2012-2016. This research is descriptive, the data used in this study using quantitative data in the form of secondary data. The technique used in data collection, is by way of documentation. Data analysis techniques are effectiveness and contribution. Data analysis method used in this research is by using descriptive analysis. The level of effectiveness of Land Ownership Tax (PBB) of Yogyakarta Year 2012-2016 as a whole shows an average of 111.596% in the criteria is very effective. The effectiveness of the acceptance of land and building acquisition rights (BPHTB) of Yogyakarta City for 2012-2016 averages 125.44% or is categorized as very effective. The contribution of land and building tax (PBB) to the local revenue (PAD) of Yogyakarta in 2012-2016 averaged 11.29% is categorized as less or low. The contribution of land and building rights tax (BPHTB) of Yogyakarta for 2012-2016 averages 13, 52% in the category of less or low. Keywords: Building Land Tax, Customs Acquisition of Land and Building Rights, Original Revenue.